Pendidikan Antikorupsi dalam Perspektif Pendidikan Agama Islam: Integrasi Nilai, Moral, dan Spiritualitas untuk Membangun Budaya Integritas - Siti Basiroh; Akbar Yusgiantara; Rustam Ibrahim (Lembaga Yasin AlSys, 2025)
Discourse on corruption in the education sector has expanded, yet studies that specifically examine the application of Islamic principles in the development of anti-corruption education remain limited. This study aims to examine the attributes of corruption in education, analyze the influence of Islamic principles in mitigating corrupt practices, and formulate solutions for the effective implementation of anti-corruption education. It employs a qualitative methodology based on literature analysis by reviewing scholarly articles, institutional reports, perspectives of Islamic education authorities, and anti-corruption policy documents. The data were analyzed using content analysis with a focus on patterns of value themes, implementation tactics, and structural barriers. The findings show that corruption in the education system is influenced by political favoritism, a lack of transparency, and deeply ingrained unethical behavior in school culture. The application of the values of trust, justice, and accountability constitutes an essential foundation for anti-corruption teaching from an Islamic perspective. These findings advance a character education paradigm grounded in religious principles and provide practical recommendations for schools in fostering a culture of honesty. The study also opens opportunities for field studies and longitudinal investigations to evaluate the effectiveness of this integrative methodology in the context of Islamic value-based anti-corruption education.